Manet's modernism : or, the face of painting in the 1980s - Fried, Michael (Chicago : University of Chicago, 1996)
Introduction: Manet before Impressionism ##1. Manet's Sources, 1859-1869 ##2. "Manet's Sources" Reconsidered ##3. The Generation of 1863 ##4. Manet in His Generation ##5. Between Realisms ##Coda: Manet's Modernism ##Appendix 1 Antonin Proust, "L'Art d'Edouard Manet" (1901) ##Appendix 2 Edmond Duranty, "Ceux qui seront les peintres" (1867) ##Appendix 3 Le Capitaine Pompilius [Carle Desnoyers], remarks on Manet (1863) ##Appendix 4 Zacharie Astruc, remarks on Manet (1863).
boek
Keywords: Manet, Edouard